Pneumatosis cystoides intestinalis as a rare cause of non-surgical pneumoperitoneum - Kotek, J; Dušek, T; Sirový, M; Odložilová, Š; Kašparová, P; Čečka, F (Rozhledy v chirurgii, 2023)
Pneumoperitoneum as a finding on imaging examinations is not always a sign of acute abdomen due to gastrointestinal perforation. These findings must be viewed in connection with the clinical condition and personal history of each patient because they may also indicate a non-surgical or spontaneous pneumoperitoneum. This condition is repeatedly described but very often neglected. This paper presents the case report of a patient with non-surgical pneumoperitoneum where, despite proceeding according to the guidelines, no expected intra-abdominal pathology explaining the patient's problems was found.
Keywords: pneumatosis cystoides intestinalis; lidé; Pneumatosis Cystoides Intestinalis; spontaneous pneumoperitoneum; pneumoperitoneum; non-surgical pneumoperitoneum; Pneumoperitoneum; Humans